2001
DOI: 10.1291/hypres.24.251
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Inhibit JNK and p38 MAPK Activation but not ERK 1/2 Activation by Angiotensin II in Rat Aortic Smooth Muscle Cells.

Abstract: Angiotensin II (Ang II) induces vascular smooth muscle cell (VSMC) hypertrophy, which results in several cardiovascular diseases. Ang II-induced cellular events have been mediated, in part, by reactive oxygen species (ROS) which also involve activation of mitogen-activated protein (MAP) kinases. Although it has been proposed that the therapeutic administration of antioxidants is useful for vascular diseases, the precise mechanisms which regulate ROS-sensitive signaling events have not been well characterized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 43 publications
0
97
1
Order By: Relevance
“…Because transfection with nox-1antisense oligonucleotides inhibited the effect of Ang II-induced superoxide generation and serum-induced VSMC proliferation (13,16), it was suggested that nox-1 is an important subunit of the NADH/NADPH oxidase in VSMCs. In an electron paramagnetic resonance (EPR) study, we also demonstrated that Ang II and endothelin stimulate • OH radical generation in VSMCs and that treatment with antioxidants inhibit these effects (17).…”
Section: Pathophysiological Role Of Oxidative Stress-mediated Bmk1 Acmentioning
confidence: 85%
“…Because transfection with nox-1antisense oligonucleotides inhibited the effect of Ang II-induced superoxide generation and serum-induced VSMC proliferation (13,16), it was suggested that nox-1 is an important subunit of the NADH/NADPH oxidase in VSMCs. In an electron paramagnetic resonance (EPR) study, we also demonstrated that Ang II and endothelin stimulate • OH radical generation in VSMCs and that treatment with antioxidants inhibit these effects (17).…”
Section: Pathophysiological Role Of Oxidative Stress-mediated Bmk1 Acmentioning
confidence: 85%
“…In fact, H 2 O 2 has been demonstrated to stimulate the activity of other transporters, namely NHE and Na/K/2Cl. NHE from Wistar [25] and SpragueDawley rat ventricular myocytes [26] were stimulated after exposure of cells to [38,39]. We previously showed that the increased intracellular H 2 O 2 in SHR PTE cells was attenuated when cells were cultured in medium supplemented with apocynin (a NADPH oxidase inhibitor) while in WKY PTE cells no effect was observed [20].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E is known to inhibit the p38 MAPK pathway in smooth muscle cells (73). Treatment with vitamin C alone enhanced the expression of phosphorylated p38 MAPK in murine melanoma cells due to an increase in intracellular region of interest levels (33).…”
Section: Discussionmentioning
confidence: 99%